DRY CURLY KOPAY CHILI (Capsicum Annum VAR. GLABIUSCUM) BY USING VAKUM OVEN STUDIED - Novitasari, Rifni (Fakultas Pertanian Prodi Teknologi Pangan, 2012)
This research about âdry curly kopay chilli (Capsicum annum var. glabiuscum) by using vakum oven studiedâ has been done in Pilot Plant Agriculture Harvest Technologi, Technologi Of Agriculture Faculty, Islamic University of Indragiri, on Desember 2010 until Pebruari 2011. The aim of this research was find the best treatment to get optimum salt dry curly copay chilli and the rehidration.Method has used in this experiment was trifaktorial whit 3 pattern of group. The treatment was : (A) pressing ; A1= without pressing A2= by pressing. The second factor (B) was level of temperature, temp of B1 = 45oC, B2 = 60oC, B3 = 75oC. The third factor (C) was timed duration, timed of C1 = 6 hour, C2 = 7 hour, C3 = 8 hour. This research to find out water solubility, percentage of Î² caroten, hot storey level, rehidration, rehidration timed and organoleptic tests by used F test then continued DNMRT (Duncan`s new multiple range test). The capcaisin just only done at once. perception to growth of microbe only presented in the form of tables. Observered of Î² caroten only in the best treatment based on organoleptik.The result showed that chili dried 75oC for 8 hour by giving press has the best treatment based organoleptik ( colour, tasted, smell). Best treatment contained water solubility 10,04%, capcisin 23%, Î² karoten 2.390,95 Î¼g/100g, The organoleptik of the best treatment compared whit import dried chili from Singapore that sold in Pekanbaru showed very significantly based on colour, significantly based on teksture and taste, non significantly based on smell.